Equinodermos pedunculados do Devoniano do Brasil e suas afinidades paleobiogeográficas - Scheffler, Sandro Marcelo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
The first occurrences of stalked echinoderms in Brazil were from the second half of the nineteenth century. Until the 1950s they were known in five Devonian formations of three major Brazilian intracratonic basins: Paraná, Amazonas, and Parnaíba. However, after the first quotes and identifications, stalked echinoderms remained for many decades without study. Only in the late twentieth century, and especially in this century, have stalked echinoderms been targets of a series of publications that greatly expanded their known morphological diversity. Currently there are almost 70 morphological patterns recognized in the Devonian. Brazilian occurrences reinforce some existing paleobiogeographicals ideas, principally related to marine currents and patterns of connections between the basins within Brazil and other parts of South America and the world. Here is also an extreme endemism in the Paraná Basin (Lower Devonian) and affinities between faunas of North Gondwana and Amazon and Parnaíba basins, in the Middle Devonian.
Keywords: Crinoidea; Blastoidea; Paleobiogeography; Brazil; South America